HUBUNGAN KEBIASAAN MENYIKAT GIGI DENGAN KARIES GIGI PADA ANAK USIA SEKOLAH - Dewi Fortuna Grace Dayanty Napitupulu (Universitas Prima Indonesia, 2023)
Caries is portrayed by a moderate sclerosing of stain and dentin designs and plaque, and it is rapidly becoming perhaps the most widely recognized persistent sickness in small kids, particularly those between the ages of 7 and 12 years. The objective of this study was to learn the association between youngsters' dental caries and brushing rehearses in Pancur Batu, Deli Serdang District, Durin Simbelang Town. This examination technique utilizes a cross-sectional procedure and a relationship plan. 84 members in this review went through accidental testing. A survey was the device utilized. The review’s discoveries demonstrate that most of the respondents have dental caries (63.1%) and unfortunate brushing propensities (57.1%), with the Chi-square trial results procuring a p-regard of 0.002 (p=0.05), showing a significant association between brushing propensities and dental caries. at the point when dental caries in small kids begin to be an issue in Durin Simbelang Pancur Batu Town, Deli Serdang District, starting in 2021. To keep away from dental caries, health professionals are obliged to show their children how to consistently keep up with oral cleanliness by cleaning and flossing their teeth.